ANALISIS TINGKAT KESUKARAN BUTIR SOAL TRY OUT BUSANA PPG BAGI GURU TERTENTU TAHAP 1 UNIVERSITAS NEGERI MALANG TAHUN 2025 - Nurul Aini; Mochammad Rizal Ramadhan; Ghaly Wijdan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the difficulty level of the PPG Clothing for Certain Teachers (BGT) tryout items for Phase 1 at Malang State University in 2025. The study subjects consisted of 68 participants with a total of 35 questions. The analysis results showed that the average difficulty level index (P) was 0.9. This value indicates that most of the questions are relatively easy, because approximately 90% of participants were able to answer correctly. Whereas in classical test theory, good instrument quality is indicated by an average difficulty index approaching 0.5 (moderate category). Thus, this condition reflects that the test instrument is not fully able to optimally differentiate participants with high and low abilities. These findings have important implications for the quality of evaluation instruments in the context of teacher professional education. Questions with a difficulty level that is too easy tend to reduce the item discrimination power, making it difficult to comprehensively measure variations in participant abilities. In addition, the presence of questions that are too easy has the potential to result in erroneous interpretations regarding participant readiness for the actual PPG exam. Therefore, improvements are needed in the preparation of test instruments. Some strategies that can be adopted include balancing the distribution of easy, medium, and difficult questions, developing questions based on Higher Order Thinking Skills (HOTS), improving the quality of distractors, and piloting questions. This will ensure the resulting instrument is more valid, reliable, and representative of the competencies of fashion teachers.